1989
DOI: 10.1093/oxfordjournals.aje.a115137
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Influenza a/Taiwan/1/86 (H1n1) Infections at a Naval Base and Its Association With Airplane Travel

Abstract: In late October 1986, an outbreak of influenza-like illness was detected at the Naval Air Station in Key West, Florida. Between October 10 and November 7, 1986, 60 active duty personnel reported experiencing a respiratory illness characterized by fever, cough, sore throat, and myalgia. Influenza A/Taiwan/1/86 (H1N1) virus was recovered from three symptomatic patients. Forty-one (68%) of 60 case-patients belonged to a 114-person squadron that had traveled to Puerto Rico for a temporary assignment from October 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
4

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 8 publications
2
59
0
4
Order By: Relevance
“…In some reported outbreaks of respiratory diseases in aircraft cabins (Klontz et al 1989;Marsden 2003;Olsen et al 2003;Kenyon et al 1996), it can be observed that many of the passengers seated in the same row or one row in front of the index patient had been infected or developed illness. From Table 1, passengers seated in these two rows generally had higher exposures than those seated further had.…”
Section: Discussionmentioning
confidence: 99%
“…In some reported outbreaks of respiratory diseases in aircraft cabins (Klontz et al 1989;Marsden 2003;Olsen et al 2003;Kenyon et al 1996), it can be observed that many of the passengers seated in the same row or one row in front of the index patient had been infected or developed illness. From Table 1, passengers seated in these two rows generally had higher exposures than those seated further had.…”
Section: Discussionmentioning
confidence: 99%
“…3 Transmission of seasonal influenza during air travel has been documented by epidemiologic investigations and is supported by model simulations. [5][6][7][8][9] Published studies of pH1N1 transmission among air travelers report that virus transmission during air travel is probable, but the risk of infection to susceptible passengers and crew may be limited, and the role of the aircraft cabin environment is unclear. [10][11][12] Documented risk factors associated with seasonal influenza virus transmission include receiving or providing health care 13 ; being in close quarters (e.g., in a household, daycare, or schools) with index patients 14 ; and close proximity to (within 1 m) or being in crowded or enclosed environments (including aircraft cabins) with an index patient who is coughing and sneezing.…”
Section: Introductionmentioning
confidence: 99%
“…A number of epidemiological investigations, e.g., Kenyon et al (1996) and Miller et al (1996), suggested that some tuberculosis outbreaks were very likely caused by airborne transmission among passengers in aircraft cabins. In-flight transmission of diseases that are believed to be transmitted by large droplets, such as severe acute respiratory syndrome (SARS) (e.g., Olsen et al 2003,) and influenza (e.g., Moser et al 1979;Klontz et al 1989), are also well documented.…”
Section: Introductionmentioning
confidence: 99%